Biotope and biocenosis of cryoconite hole ecosystems on Ecology Glacier in the maritime Antarctic - Buda, Jakub; Łokas, Edyta; Pietryka, Mirosława; Richter, Dorota; Magowski, Wojciech; Iakovenko, Nataliia S.; Porazinska, Dorota L.; Budzik, Tomasz; Grabiec, Mariusz; Grzesiak, Jakub; Klimaszyk, Piotr; Gaca, Paweł; et al. (Science of The Total Environment, 2020)
Despite recent great interest in glacier ecosystems in the continental Antarctic, little is known about their maritime counterparts. Our study presents descriptive data on cryoconite sediments and cryoconite holes on Ecology Glacier (King George Island) to accomplish three main objectives: (a) to identify main eukaryotic (algae, invertebrates) and prokaryotic (cyanobacteria) components of microbial communities; (b) to provide a “baseline” of community composition, organic matter and artificial contamination; and (c) to identify key abiotic factors that might be important in community assembly. Cryoconite holes were sampled along an altitudinal gradient of Ecology Glacier in January, mid Austral Summer 2017. Cryoconite holes located in lower altitude were deeper than those located in the middle and the highest altitude. Seventeen species of algae and cyanobacteria with biomass of 0.79 to 5.37 μg/cm3 have been found in sediments. Dominant species were cyanobacterial Pseudanabaena frigida and Bacillariophyceae Microcostaus sp. Biomass of Bacillariophyceae was significantly higher than that of Chlorophyta and Cyanobacteria. We found three species of rotifers (potentially two new to science) and for the first time a glacier dwelling Acari (suspension feeder, Nanorchestes nivalis). Organic matter content ranged from 5.4% to 7.6%. Investigated artificial radionuclides included 137Cs, 238Pu, 239+240Pu and 241Am. 210Pb seems to be related to organic matter content. Overall, cryoconite holes on Ecology Glacier present unique habitats that serve as biodiversity hotspots of psychrophiles, source of organic matter, matrices for radioactivity tracking and model for observing changes in supraglacial ecosystems in the maritime Antarctic.